Arahan Pengendalian Parkir Badan Jalan Pada Kawasan Komersial Di Jalan Kolonel Abundjani Kota Jambi - Rahma Dwi Cahyani; Mardwi Rahdriawan (Jurusan Perencanaan Wilayah dan Kota, 2017)
The excessive number of activities on Jalan Kolonel Abundjani Corridor makes parking activity’s arrangement urgently needed to improve the existing paring performance. If not, eventually it will cause irregular vehicle circulatory and traffic congestion, moreover the increasing number of people using private vehicle. This study aims to formulate the proposal improvement in parking arrangement based on need. The research methid in this study are secondary data collected from theories and study of literature in finding the research variables, while the primary data collected from field observation and interview. Parking space for four-wheeled vehicle needs to add as many as 16.762 or 9.58%. the needs for parking space for the next 5 (five) years by the year 2022 for four-wheeled vehicle. So that using calculation of parking space area needed on Jalan Kolonel Abundjani which are 74.338 m2 for two-wheeled vehicle and 82.975 m2 for four-wheeled vehicle. The proposal parking improvement based on sufficient road width on the west side and est side of Jalan Kolonel Abundjani which is 6 meters allows on-street parking with 00 angles if the existing parking space is packed, but doesn’t allow double parking because the effective road width has been reduced. Parking location that considered feasible located in two places. The first located in region A precisely at location point A2 with walking distance ±320 meters in each point. The second location is region B precisely at location point B3 with walking distance ±310 meters in each point.